P7 Occupational eosinophilic constrictive bronchiolitis with asthma in a foam cutter caused by Soya bean products. (16th November 2010) - Hoyle, J; Ballance, K; Francis, H; Pickering, CAC; Niven, RMc
Abstract : Introduction and background: Soya bean dust is a recognised cause of asthma. More recently Soya bean has bean used in the manufacture of foam. The main market for this 'environmentally friendly foam' is for cot mattresses. We describe a case of occupational asthma with eosinophilic constrictive bronchioloitis caused by cutting foam manufactured using Soya bean. This is the first case in world literature to the authors′ knowledge where Soya bean induced respiratory allergy has been described in this way. Case description: 26-year male smoker presents with a 3-month history of fatigue, 10 kg weight loss, cough and work related breathlessness. Soya-based foam had been introduced into the work place 6 months prior to presentation, which the subject cut with a band knife. No respiratory protection or ventilation was used. No previous allergies or asthma were known. Throat itch preceded symptom onset. Other workers complained of conjunctivitis. At presentation the subject was apyrexial, oxygen sats 88% air, CRP 0.7, peripheral eosinophils 1.6 (14%), WBC normal and FEV1 34% predicted. Vasculitis and HIV screening negative. HRCT confirmed constrictive bronchiolitis, which resolved after a course of oral steroids. Lung function returned to normal. The subject was re-introduced to work where a marked drop in FEV1 was documented (Abstract P7 Figure 1 ). Bronchoscopy showed mucus plugging with eosinophilic casts. Peripheral eosinophilia increased with general fatigue. Total IgE remained normal, IgE for Aspergillus fumigatus <0.4. IgE for soya was 0.4, but slightly elevated for other cross reactants. Skin tests for Soya bean and husk were positive. The worker was redeployed away from the foam cutting area but still had occasional exposure and peak flow variability compatible with occupational asthma, with increased non-specific bronchial hyper-reactivity on histamine challenge. Lung function, eosinophil count and bronchial reactivity stabilised following removal of the foam from the factory and home. Conclusion: Eosinophilic airway plugging, with severe air trapping, reversible airflow obstruction and peripheral eosinophilia resolved after removing Soya bean based foam products from the work area and home. Skin prick tests confirm Soya bean allergy. The syndrome described has not been reported previously and may have implications for the foam manufacturing industry.